Ang sekreto ng magagarang bula the secret of fantastic bubbles - Balce, Marina E.; Balce, Niccolo E. (Quezon City University of the Philippines National Institute for Science and Mathematics Education Development (UP NISMED), 2014)
"Who hasn't played with soap bubbles? Everyone must have enjoyed playing with them. Through the story "The Secret of Fantastic Bubbles," two messages are shown. First, we should know how to think which are within our abilities and which are suited to our environment. Blind copying is not good because it can strain relationships and cause undue frustrations. Second, we should have the habit of giving priority to doing important things. And we should do those important things first in our list of things to do. But what really are considered important things? In this story, an example of a very important thing to do is given especially among community leaders: keep the environment clean and green."--Preface.
"Sa Filipino at Ingles."--Cover.
Keywords: Reading (Primary).; Children's stories, Filipino